A study to evaluate breastfeeding practices among lactating mothers: a community based study in rural anganwadi centers in field practice area of government medical college, - Singh, Nisha; Chouhan, Yogendra; Trivedi, Anshuli; Patel, Seema; Sethia, Soumitra (International Journal Of Community Medicine And Public Health, 2016)
Background: Feeding the baby exclusively on breast milk, without any other source of nutrition for a period of 6 months is called exclusive breast feeding. A child who is breast fed has greater chances of survival than a child artificially fed. The data suggests that infant mortality rates in developing countries are 5-10 times higher among children who have not been breast fed or have been breast fed for less than 6 months. Despite the marked advantages of breast feeding, its popularity has declined significantly in many parts of the world including India. The main objectives were (1) to assess breastfeeding practices prevalent amongst lactating mothers; (2) to identify misconceptions regarding failure to adopt exclusive breast feeding and weaning; (3) To counsel and motivate mothers for exclusive breastfeeding. Methods: Mixed methods study (qualitative cum quantitative). 60 lactating mothers were interviewed and their knowledge and awareness on breast feeding was assessed through a pre-designed, semi-open questionnaire. Focused Group Discussions (FGD) were also conducted among Lactating Mothers, their Mothers or Mother in laws at Anganwadi centers of selected sites. Results: 63.34% mothers did colostrum feeding. Only 45% of them breastfed exclusively. 48.33% gave prelacteal feeds like honey and water. LSCS was major cause of delayed initiation of breastfeeding. Many agreed regarding non supportive attitude from family. Majority of mothers had poor knowledge regarding proper positioning and attachment while breastfeeding. Conclusions: Proper counseling and training of mothers must be done at the time of delivery by the doctors and the nursing staff regarding breastfeeding practices. Anganwadi workers must also actively counsel the mothers regarding exclusive breast feeding. Supporting women who are self-employed or who work in the informal economy is required.